PEWARISAN BAGI WARGA NEGARA INDONESIA KETURUNAN TIONGHOA DI KOTA PEKALONGAN - Isti sulistyorini (LPPM Universitas Pekalongan, 2014)
Chinese (Tionghoa) is one of groups of citizen that based on the rule article 131 IS have civil law. Being involved in that law, there are some difficulties faced by the Chinese (Tionghoa). The difficulties are in line to the sistems of cultures and belief they have which are very different from the European. The aims of this research are to find out the way of giving heritage from the ascendance or the tendencyto decide it that has been done by the Indonesian-Tionghoa in Pekalongan and the ways to solve the problems caused by it. This is a descriptive qualitative research approach. the researcher found out the primer and secondary data in descriptive ways to have the objectives of the research. The result of the research shows that the way of giving heritage done by the Indonesian-Tionghoa in Pekalongan based on the law used is that the position in family level between men dan women is the same so that they will have the same opportunities and qualitities of wealth from the ascendances. If there are problema due to the heritage giving, the family will have a discussion to solve it. If it cannot be solved well so they can bring it to court. Key word : heritage giving, Tionghoa, vicil law.